Retrieval Does Not Always Enhance Suggestibility: Testing Can Improve Witness Identification Performance - Chan, Jason C.K. (Law and human behavior, 2012)
Verbally recalling the appearance of a perpetrator and the details of an event can sometimes hinder later eyewitness memory performance. In two experiments, we investigated the effects of verbally recalling a face on people's ability to resist subsequent misinformation about that face. Participants watched a video of a theft and then completed either a recall test or a distractor activity. After a delay, some participants heard a piece of misinformation. Memory was assessed with a recall test in Experiment 1 and with a target-present lineup in Experiment 2. In both experiments, initial testing reduced eyewitness suggestibility for the face. (PsycINFO Database Record (c) 2012 APA, all rights reserved